2011
DOI: 10.1139/tcsme-2011-0006
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations of a Rotor System With Multiple Coupler Offsets

Abstract: In this paper, a transfer matrix method (TMM) for rotors with multiple coupler offsets was derived. The studies showed the coupler's stiffness altered the rotor's critical speeds but offset caused additional external excitation. The cases of two offsets in-and anti-phase in a typical rotor were given as examples. In the in-phase case, significantly increased response amplitude occurred at lower rotational speed and the increase was linearly proportional to the offset value. As to the anti-phase case, the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Namely, severe misalignment and rotating looseness (the gap between bearing nonrotating and rotating parts) have similar frequency spectrum characteristics [3][4][5]. Multiple theoretical [2,6,7] and experimental research have confirmed the main characteristics of the vibrations caused by the faults of shafts mis-alignment [8][9][10], and rotational looseness [11][12][13]. As main confirmation was that both faults have similar frequency spectrums with multiples of the rotational frequency.…”
Section: Introductionmentioning
confidence: 91%
“…Namely, severe misalignment and rotating looseness (the gap between bearing nonrotating and rotating parts) have similar frequency spectrum characteristics [3][4][5]. Multiple theoretical [2,6,7] and experimental research have confirmed the main characteristics of the vibrations caused by the faults of shafts mis-alignment [8][9][10], and rotational looseness [11][12][13]. As main confirmation was that both faults have similar frequency spectrums with multiples of the rotational frequency.…”
Section: Introductionmentioning
confidence: 91%